2011
DOI: 10.1007/s11676-011-0196-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of existing agroforestry practices in Madhupur Sal forest: an assessment based on ecological and economic perspectives

Abstract: A study was conducted in Madhupur sal forest of Tangail, Bangladesh to identify the suitable agroforestry practices of the area.Considering the ecological aspects of different agroforestry practices 10 sample plots (10 m × 10 m) from each land uses were taken, including natural forest to get a comparative scenario. The study showed that among the different agroforestry practices, Margalef and ShannonWeiner index values are the maximum for pineapple agroforestry and lower for banana agroforestry, and Evenness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
(18 reference statements)
4
22
0
Order By: Relevance
“…A few researches have estimated above-ground forest C stocks in Bangladesh. C stocks were found to vary with land uses, including mangrove and coastal (99 Mg C ha -1 ; [22]), protected contiguous and fragmented (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) Mg C ha -1 ; [15]), bamboo (53 Mg C ha -1 ; [23]), hill (103 Mg C ha -1 ; [16]) and homestead (53 Mg C ha -1 ; [17]) forests. These C stocks have been found to be dependent on the stand structure (e.g., tree height, DBH, density, basal area) [24,25] and tree species [26,27], and stands with fast-growing tropical tree species having the highest forest C stocks (201 Mg C ha -1 ; [28]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few researches have estimated above-ground forest C stocks in Bangladesh. C stocks were found to vary with land uses, including mangrove and coastal (99 Mg C ha -1 ; [22]), protected contiguous and fragmented (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) Mg C ha -1 ; [15]), bamboo (53 Mg C ha -1 ; [23]), hill (103 Mg C ha -1 ; [16]) and homestead (53 Mg C ha -1 ; [17]) forests. These C stocks have been found to be dependent on the stand structure (e.g., tree height, DBH, density, basal area) [24,25] and tree species [26,27], and stands with fast-growing tropical tree species having the highest forest C stocks (201 Mg C ha -1 ; [28]).…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, soil C concentration has been found variable (1-16 mg g -1 ), mainly responsible to the site and depth in soil [39,40]. Soil C stocks estimated in Bangladesh were 23 Mg C ha -1 in semievergreen [41], 34 Mg C ha -1 in mangrove [22], and 59 Mg C ha -1 in deciduous [42] forests. Earlier, changes in stand structure and litter quality have found to modify the soil C dynamics in agroforestry ecosystems and also in tropical homestead forests [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Thus a lot of phytosociological studies have been conducted throughout the world to understand the structure of different forest communities (Campbell et al, 1986;Timilsina et al, 2007;Top et al, 2009;Sambare et al, 2011;Erenso et al, 2014). In Indian scenario, several phytosociological studies have also been performed in different tropical forests: Western India (Sharma and Upadhyaya, 2002;Panchal and Pandey, 2004;Krishna et al, 2014), Peninsular India (Parthasarathy et al, 1992;Visalakshi, 1995;Parthasarathy, 1999;Mani and Parthasarathy, 2005;Gunaga et al, 2013), North East India (Bhuyan et al, 2003;Kumar et al, 2006;Kibria and Saha, 2011;Sarkar and Devi, 2014) and Northern India (Singh and Singh, 1991;Sagar et al, 2003;Pandey and Shukla, 2003;Chauhan et al, 2008;Tripathi and Singh, 2009;Behera et al, 2012). In Northern Indian forests, furthermost studies have been executed in the tropical dry deciduous forests of Vindhyan region (Jha and Singh, 1990;Sagar and Singh, 2006;Sagar et al, 2008) and tropical moist deciduous forests of the Terai region (Pandey and Shukla, 1999;Shukla, 2009;Res.…”
Section: Introductionmentioning
confidence: 99%
“…The local farmer of the Madhupur Garh area relies on agroforestry practices that play a vital role in offering multiple alternatives and opportunities with a view to improving farm production and income and also providing productive and conservation functions to the ecosystems (Alam et al, 2010). Some researchers have noted the benefits of Mango, Banana, Pineapple, Lemon, Jackfruit, and different seasonal crops cultivation along with agroforestry practices at the Madhupur Garh area (Akter et al, 2020;Rana, 2017;Kibria and Saha, 2011;Roy et al, 2011;Hasan et al, 2008;Safa, 2004). Farmers of Bangladesh, like many other Asian countries, have been growing cereals, root crops, fiber, vegetables, and fruit in association with the trees and another woody perennial (Alam et al, 1990).…”
mentioning
confidence: 99%
“…Scientists and experts have worked with farmers throughout the world to identify and develop improved agroforestry practices that build on local practices and offer substantial benefits to communities and to the environment (Franzel and Scherr, 2002). The most important crop and tree products from the Madhupur Garh areas agroforestry practices are Pineapples, Ginger, Aroid, Turmeric, Banana, Papaya and poles, pulpwood and firewood as these trees are mostly shortrotation species (Ghosh et al, 2011;Islam et al, 2013;Chakraborty et al, 2015;Kibria and Saha, 2011). In Bangladesh, it is revealed that about 2% family income comes from Agroforestry practices (Chakraborty et al, 2015); however, the agroforestry programs at the Madhupur Sal forest area contributed more than 46% of the forest dependents people's household income (Islam et al, 2011).…”
mentioning
confidence: 99%